2021
DOI: 10.1088/2058-6272/ac15ee
|View full text |Cite
|
Sign up to set email alerts
|

Improving the surface flashover performance of epoxy resin by plasma treatment: a comparison of fluorination and silicon deposition under different modes

Abstract: This work treats the Al 2 O 3 -ER sample surface using dielectric barrier discharge fluorination (DBD-F), DBD silicon deposition (DBD-Si), atmospheric-pressure plasma jet fluorination (APPJ-F) and APPJ silicon deposition (APPJ-Si). By comparing the surface morphology, chemical components and electrical parameters, the diverse mechanisms of different plasma modification methods used to improve flashover performance are revealed. The results show that the flashover voltage of the DBD-F samples is the largest (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…According to the high‐resolution F 1s spectrum of F‐PPTA@PP separator, the two main peaks located at 686.7 and 688.1 eV correspond to CF and CF x ( x = 2 and 3) bonding, respectively (Figure S7c, Supporting Information), indicating that the CF bonds are the primary F‐containing groups existing on the F‐PPTA@PP separator. [ 45–46 ] CF bond, as the strongest single covalent bond (488 kJ mol –1 ), [ 31 ] is able to not only provide maximum charge polarization for enhancing electrochemical activity of energy‐related reactions, [ 32 ] but also significantly improve the electrolyte affinity of separators. [ 47 ] As proven in the insets of Figure 2a–c, the electrolyte contact angle on the F‐PPTA@PP separator (18.5°) was significantly smaller than that on the PPTA@PP (40.5°) and PP (44.1°) separators.…”
Section: Resultsmentioning
confidence: 99%
“…According to the high‐resolution F 1s spectrum of F‐PPTA@PP separator, the two main peaks located at 686.7 and 688.1 eV correspond to CF and CF x ( x = 2 and 3) bonding, respectively (Figure S7c, Supporting Information), indicating that the CF bonds are the primary F‐containing groups existing on the F‐PPTA@PP separator. [ 45–46 ] CF bond, as the strongest single covalent bond (488 kJ mol –1 ), [ 31 ] is able to not only provide maximum charge polarization for enhancing electrochemical activity of energy‐related reactions, [ 32 ] but also significantly improve the electrolyte affinity of separators. [ 47 ] As proven in the insets of Figure 2a–c, the electrolyte contact angle on the F‐PPTA@PP separator (18.5°) was significantly smaller than that on the PPTA@PP (40.5°) and PP (44.1°) separators.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of shallow traps on surface flashover: Shallow surface traps are also a crucial factor influencing surface flashover. Xie et al [168] used an atmospheric pressure plasma junction (APPJ) method to fluorinate and deposit Si on epoxy/Al 2 O 3 composites. They found that the energy depth and density of deep surface traps decrease while the energy depth of shallow surface traps decreases, but their density increases as the treatment time increase, causing an increase in DC surface flashover with the treatment time.…”
Section: Effects Of Surface Traps On Surface Flashovermentioning
confidence: 99%
“…(a) Schematic of the energy band structures of polymeric materials [77]. (b) Relationships between V f and surface trap parameters, that is, (b‐i) deep surface trap level [70, 71, 114, 167], (b‐ii) deep surface trap density [71, 95, 114, 167], (b‐iii) shallow surface trap level [71, 145, 152, 160, 168], and (b‐iv) shallow surface trap density [71, 145]. (c) ‘U‐shaped’ dependence of V f on surface trap level.…”
Section: Competing Mechanisms Of Charge Transport In Surface Flashovermentioning
confidence: 99%
See 1 more Smart Citation
“…The declined charge density and accelerated carrier mobility were the main outcomes of their research which proves the effectiveness of fluorination to improve the insulation strength of polymer dielectrics. Similarly, Y. Huang et al and J. Yan et al adopted electron beam and plasma treatment methods, respectively, to alter the surface condition of epoxy composites [16,17]. The authors claimed that the augmented roughness and conductivity of the surface were obtained after plasma modification and were the key factors to reduce the charging capability of epoxy composites.…”
Section: Introductionmentioning
confidence: 99%